2018
DOI: 10.1002/micr.30320
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative evaluation of perfusion in free flap surgery: A systematic review and meta‐analysis

Abstract: Based on the current literature, FI and laser Doppler are most suitable to intraoperatively measure free flap tissue perfusion, resulting in improved flap survival. However, this review was limited by the available literature. Additional studies are necessary to investigate the predictive value of intraoperative perfusion measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 88 publications
(465 reference statements)
1
55
0
Order By: Relevance
“…In line with this, Smit et al recently published a systematic review and meta-analysis on intraoperative evaluation of perfusion in free flap surgery. 25 We fully agree with their conclusion that ICG-NIR-VA is one of the most suitable methods to measure intraoperative free flap tissue perfusion, resulting in improved free flap survival. 25 In our previous study, ICG-NIR-VA predicted full tissue viability in all flaps which healed uneventfully but also predicted the exact extent of tissue necrosis in flaps with partial flap necrosis.…”
Section: Discussionsupporting
confidence: 82%
“…In line with this, Smit et al recently published a systematic review and meta-analysis on intraoperative evaluation of perfusion in free flap surgery. 25 We fully agree with their conclusion that ICG-NIR-VA is one of the most suitable methods to measure intraoperative free flap tissue perfusion, resulting in improved free flap survival. 25 In our previous study, ICG-NIR-VA predicted full tissue viability in all flaps which healed uneventfully but also predicted the exact extent of tissue necrosis in flaps with partial flap necrosis.…”
Section: Discussionsupporting
confidence: 82%
“…A meta-analysis by Smit et al concluded that fluorescent imaging and laser Dopplers are the most suitable modalities for intraoperative free flap tissue perfusion assessment and that utilizing them can improve flap survival. 6 …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that fluorescence imaging and laser Doppler are the most suitable methods to assess tissue perfusion in free flaps. 6 As for the pedicle TRAM flap, the use of indocyanine green (ICG) fluorescence imaging has been reported by Yamaguchi et al as a safe, quick, and accurate technique of flap perfusion analysis and may reduce fat necrosis. 7 However, there is currently no study that describes the vascular distribution in the subcutaneous fat layer of the zone 4 border identified by the ICG technique.…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed the metabolic changes in bone tissue after a period of ischemia (intraoperatively and during the first 5 days postsurgery). In a recent review of objective methods for the intraoperative assessment of free flap perfusion, Smit et al () cited only one article on microdialysis (Edsander‐Nord, Röjdmark, & Wickman, ) and concluded that additional studies were necessary.…”
Section: Discussionmentioning
confidence: 99%